Tinjauan Yuridis Penyelesaian Sengketa Perjanjian Waralaba (Franchise): Studi Putusan Nomor 2297 K/Pdt/2012 - Munthe, Tanty SriAulia; Bara, Ismed Batu (Rechtsnormen Jurnal Komunikasi dan Informasi Hukum, 2022)
The franchise business system is currently widely used by entrepreneurs who are starting businesses in Indonesia. Not only big entrepreneurs have used this franchise business system, but also this franchise business system has also been used by lower and middle entrepreneurs. This is a very good first step to promote existing business in Indonesia. This business style originating from the United States is very suitable for use in Indonesia, because the system has similarities with the character of the Indonesian people, namely the mutual cooperation system. This franchise business system is considered easy and fast in starting a business for entrepreneurs who are just starting their business without requiring a lot of capital and can reduce greater risk